2013
DOI: 10.1039/c3ob41485j
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-functionalized water-soluble nanoparticles for biomimetic nucleophilic/general-base catalysis under acidic conditions

Abstract: Cross-linking the micelles of 4-dodecyloxybenzyltripropargylammonium bromide by 1,4-diazidobutane-2,3-diol in the presence of azide-functionalized imidazole derivatives yielded surface-cross-linked micelles (SCMs) with imidazole groups on the surface. The resulting water-soluble nanoparticles were found, by fluorescence spectroscopy, to contain hydrophobic binding sites. The imidazole groups promoted the photo-deprotonation of 2-naphthol at pH 6 and catalyzed the hydrolysis of p-nitrophenylacetate (PNPA) in aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…95 Besides the well-established hydrolysis of activated esters it was shown that imidazole and/or histidine can catalyse other reaction types: the aldol reaction (enamine-mediated, described above), hydrolysis of N-acetylserinamide, RNA cleavage, thioester hydrolysis, amongst others. 95 Additionally, several studies showed effective catalysts designs with imidazole/ histidine residues as part of a nanoparticle 96 , polymer 97,98 or protein 93,[99][100][101] . Remarkably, in 2000, Chen described Ser-His as a minimalistic enzyme for amide hydrolysis 102 , yet follow-up research proved Ser-His is only able to catalyse activated ester hydrolysis (similar to imidazole activity).…”
Section: Nucleophilic and General/specific Base Catalysismentioning
confidence: 99%
“…95 Besides the well-established hydrolysis of activated esters it was shown that imidazole and/or histidine can catalyse other reaction types: the aldol reaction (enamine-mediated, described above), hydrolysis of N-acetylserinamide, RNA cleavage, thioester hydrolysis, amongst others. 95 Additionally, several studies showed effective catalysts designs with imidazole/ histidine residues as part of a nanoparticle 96 , polymer 97,98 or protein 93,[99][100][101] . Remarkably, in 2000, Chen described Ser-His as a minimalistic enzyme for amide hydrolysis 102 , yet follow-up research proved Ser-His is only able to catalyse activated ester hydrolysis (similar to imidazole activity).…”
Section: Nucleophilic and General/specific Base Catalysismentioning
confidence: 99%
“…Molecular imprinting in surfactant micelles is a powerful method to create nanoparticle receptors that resemble water‐soluble proteins. Their hydrophilic exterior,10a,c,d,g hydrophobic core,26 and internal tailor‐made binding sites11 all could be tuned easily with the surface‐cross‐linked micelle platform. Previous noncovalent imprinting in the micelles only yielded hydrophobic pockets with predefined shape and size 11.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers put considerable effort to design the synthetic mimic of esterase using de novo design 26,27 , dendrimer 28 , polymer 29 , membrane 30,31 , selfassembling peptides 32,33 , nanofibers 34 and amyloid fibrils 5,33,35 to cleave an ester at the physiological condition. However, most of the designs are only able to cleave the active ester like p-nitrophenol ester 5,27,[29][30][31][32][33][34][35][36] and remain ineffective towards normal non-activated esters 37 . Thus, it is still challenging to hydrolyze an unactivated ester at physiological pH and new methods are being developed 37 .…”
Section: Mainmentioning
confidence: 99%
“…While an ester usually be hydrolyzed at basic pH and at elevated temperature, the catalytic triad of esterase performs similar reaction at neutral buffer solution (pH ~7.0) and at physiological temperature 24,25 . Researchers put considerable effort to design the synthetic mimic of esterase using de novo design 26,27 , dendrimer 28 , polymer 29 , membrane 30,31 , selfassembling peptides 32,33 , nanofibers 34 and amyloid fibrils 5,33,35 to cleave an ester at the physiological condition. However, most of the designs are only able to cleave the active ester like p-nitrophenol ester 5,27,[29][30][31][32][33][34][35][36] and remain ineffective towards normal non-activated esters 37 .…”
mentioning
confidence: 99%